Analysing Service Quality Control with SQC Methods to Improving Customer Satisfaction - Salsa Ayu Aziah; Karnowahadi; Sri Marhaeni Salsiyah (Politeknik Negeri Semarang, 2024)
The perception gap between customer expectations and the quality of service received is a profound challenge for a business. This gap can arise when customers have high expectations for services, but the quality provided by the business does not reach or exceed expectations. This study aims to control service quality at PT Taspen (Persero) KCU Semarang by providing recommendations or proposals using the statistical quality control (SQC) method approach as a statistical tool to improve customer satisfaction. With data collection techniques used are inspection sheets, histograms, P - control charts, pareto diagrams, flow charts, cause - effect diagrams and proposed improvements based on cause - effect diagrams. The respondents obtained were 84 respondents, so the calculations and analyses produced were the number of complaints in January, February, March, April as many as 56 complaints, with the types of facility complaints of 44.64%, service reliability complaints of 21.43%, employee responsiveness complaints of 10.71%, problem solving complaints of 10.71%, and empathy complaints of 12.50% with doinan causal factors are human factors, method factors, and material factors. Gap persepsi antara harapan pelanggan dan kualitas pelayanan yang diterima menjadi tantangan mendalam bagi suatu bisnis. Kesenjangan ini dapat muncul ketika pelanggan memiliki harapan yang tinggi terhadap pelayanan, namun kualitas yang diberikan oleh bisnis tidak mencapai atau melebihi ekspektasi. Penelitian ini bertujuan mengendalikan kualitas pelayanan pada PT Taspen (Persero) KCU Semarang dengan memberikan rekomendasi atau usulan menggunakan pendekatan metode statistical quality control (SQC) sebagai alat statistik untuk meningkatkan kepuasan pelanggan. Dengan teknik pengumpulan data yang digunakan adalah lembar pemeriksaan, histogram, P – chart control, diagram pareto, diagram alur, diagram sebab – akibat dan usulan perbaikan berdasarkan diagram sebab – akibat. Responden yang diperoleh adalah sebanyak 84 responden, maka perhitungan dan analisis yang dihasilkan adalah jumlah komplain pada Bulan Januari, Februari, Maret, April sebanyak 56 komplain, dengan jenis komplain fasilitas sebesar 44.64%, komplain kehandalan pelayanan sebesar 21.43%, komplain daya tanggap pegawai sebesar 10.71%, komplain penyelesaian masalah sebesar 10.71%, dan komplain empati sebesar 12.50% dengan faktor penyebab yang doinan adalah faktor manusia, faktor metode, dan faktor material.